HISTORICAL AND CONTEMPORARY DEVELOPMENTS IN THE EDUCATION SYSTEMS OF ENGLAND, WALES, SCOTLAND, AND NORTHERN IRELAND - Abdurakhmanov Turakhon Saydullayevich; Mominjonova Rahimaxon (TADQIQOTLAR, 2025)
Abstract:This article explores the evolution of the education systems in England, Wales, Scotland, and Northern Ireland from their historical roots to the modern-day structures. It highlights the unique characteristics of each region’s system, influenced by their political autonomy and cultural identity. The article also discusses recent changes in curricula, assessments, governance, and technology integration in schools, and analyses how these reforms aim to improve equity, quality, and inclusivity across the United Kingdom.